Metabolic alteration in obese diabetes rats upon treatment with Centella asiatica extract - Maulidiani, H; Abas, Faridah; Khatib, Alfi; Perumal, Vikneswari; Suppaiah, V; Ismail, A; Hamid, M; Shaari, Khozirah; Lajis, NH (Elsevier Ireland Ltd, 2016)
Ethnopharmacological relevance